Body condition influences ontogeny of foraging behavior in juvenile southern elephant seals. Issue 1 (18th December 2018) - Orgeret, Florian; Cox, Sam L.; Weimerskirch, Henri; Guinet, Christophe
Abstract: Ontogeny of diving and foraging behavior in marine top predators is poorly understood despite its importance in population recruitment. This lack of knowledge is partly due to the difficulties of monitoring juveniles in the wild, which is linked to high mortality early in life. Pinnipeds are good models for studying the development of foraging behaviors because juveniles are large enough to robustly carry tracking devices for many months. Moreover, parental assistance is absent after a juvenile departs for its first foraging trip, minimizing confounding effects of parental input on the development of foraging skills. In this study, we tracked 20 newly weaned juvenile southern elephant seals from Kerguelen Islands for up to 338 days during their first trip at sea following weaning. We used a new generation of satellite relay tags, which allow for the transmission of dive, accelerometer, and location data. We also monitored, at the same time, nine adult females from the colony during their post‐breeding trips, in order to compare diving and foraging behaviors. Juveniles showed a gradual improvement through time in their foraging skills. Like adults females, they remarkably adjusted their swimming effort according to temporal changes in buoyancy (i.e., a proxy of their body condition). They also did not appear to exceed their aerobic physiological diving limits, although dives were constrained by their smaller size compared to adults. Changes in buoyancy appeared to also influence their decision to either keep foraging or return to land, alongside the duration of their haul outs and choice of foraging habitat (oceanic vs. plateau). Further studies are thus needed to better understand how patterns in juveniles survival, and therefore elephant seal populations, might be affected by their changes in foraging skills and changes in their environmental conditions. Abstract : Innovative on‐board satellite relay data tags have allowed to monitor the ontogeny of foraging behaviour in 20 juveniles elephant seals for almost one year. Their change in body condition and buoyancy had a large influence on the improvement of their foraging and diving behaviour. Some individuals that did not manage to improve their body condition probably died at sea, this confirms that the early life of juveniles of deep marine air‐breathing predators is a critical phase for the future of the populations.